Modern radio production - O'Donnell, Lewis B.; Benoit, Philip;Hausman, Carl (California : Wadsworth Publishing Company, 1986)
This book will introduce you to the fascinating and challenging field of radio production.
Part One. The tools -- Part Two. The techniques -- Part Three. The application.
Includes index.
Keywords: RADIO BROADCASTING